Pensiero e retropensiero. Limiti e legittimità della critica antisionista al vaglio della Corte Europea dei Diritti dell’Uomo (Stato, Chiese e pluralismo confessionale, 2024)
Thought and counter-thought. The limits and legitimacy of Israel-critical speech under the European Court of Human RightsABSTRACT: In May 2016, the International Holocaust Remembrance Alliance (IHRA) adopted a working definition of antisemitism as a non-binding guide for states and policymakers to identify criminal anti-Jewish behaviour. Critics, however, argue that the IHRA definition hastily conflates illegitimate forms of antisemitism with legitimate political speech against Israel's government and policies. Therefore, if integrated into national legislation, they warn that the IHRA definition could easily become a legal tool to stifle critics of the Israeli government and advocates for Palestinian rights. Political agendas apart, the terminological imprecision of the IHRA definition raises timely questions about the boundaries between antisemitism and anti-Zionism, as well as between legitimate and illegitimate Israel-critical speech. This is especially relevant, particularly after Palestinian militant group Ḥamās launched a surprise attack against Israel on October 7, 2023. The ongoing war thus raises the questions: Apart from open calls to violence, how to assess when legitimate, anti-Israel speech might spiral into illegitimate, harmful discourses? And what factors should be brought to bear on legal balancing? Although not dealing with a war-torn scenario, the European Court of Human Rights (ECtHR) has offered some insights on the issue that will be addressed in this paper.SOMMARIO: 1. Introduzione - 2. Legittimità della critica antisionista: Baldassi c. Francia - 3. Limiti della critica antisionista: status pubblico del divulgatore e natura antisemita della divulgazione - 3.1. Bonnet c. Francia - 4. Conclusioni.